2021
DOI: 10.3389/fmolb.2021.647424
|View full text |Cite
|
Sign up to set email alerts
|

ML-AdVInfect: A Machine-Learning Based Adenoviral Infection Predictor

Abstract: Adenoviruses (AdVs) constitute a diverse family with many pathogenic types that infect a broad range of hosts. Understanding the pathogenesis of adenoviral infections is not only clinically relevant but also important to elucidate the potential use of AdVs as vectors in therapeutic applications. For an adenoviral infection to occur, attachment of the viral ligand to a cellular receptor on the host organism is a prerequisite and, in this sense, it is a criterion to decide whether an adenoviral infection can pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Small molecule information is often represented using a simplified molecular-input lineentry system (smiles). 27 In such a setting ML can assist in RNA and DNA accessibility analysis, transcription analysis (reviewed in 28 ), protein-protein interactions, [11][12][13]29 as well as, sequence-based host organism or receptor prediction. 14 Noteworthy, in well-defined tasks simple ML algorithms like Random Forest (RF) 30 classification, Multilayer Perceptron (MLP) or kernel-based SVM 31 perform remarkably well.…”
Section: Host-pathogen Interactions Analysis From Genetic and Molecular Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule information is often represented using a simplified molecular-input lineentry system (smiles). 27 In such a setting ML can assist in RNA and DNA accessibility analysis, transcription analysis (reviewed in 28 ), protein-protein interactions, [11][12][13]29 as well as, sequence-based host organism or receptor prediction. 14 Noteworthy, in well-defined tasks simple ML algorithms like Random Forest (RF) 30 classification, Multilayer Perceptron (MLP) or kernel-based SVM 31 perform remarkably well.…”
Section: Host-pathogen Interactions Analysis From Genetic and Molecular Datamentioning
confidence: 99%
“…For example, Karabulut et al show that on the task of adenovirus infection genus prediction kernel-based SVM reaches performance of 0.96 F1 score and 0.89 area under the receiver operating characteristics curve (AUC) with RF and MLP algorithms trailing remarkably close. 29 In such cases, more advanced algorithms like DL are not very likely to deliver a significant further improvement. However, in the settings outside of the very specific data set these algorithms may deliver a boost in generalization.…”
Section: Host-pathogen Interactions Analysis From Genetic and Molecular Datamentioning
confidence: 99%
“…Researchers have developed a machine learning based clustering applications to distinguish several microbial pathogens ( 24 , 25 ) and classification applications to categorize the genes associated with the survival of pathogens under certain environmental conditions, antibiotics, or other disturbances ( 26 ). Similarly, researchers have developed classification applications to determine VHPPIs that play a key role in understanding the functional paradigms of viruses as well as host responses ( 27 , 28 ). With an aim to provide cheap, fast, and accurate virus-host protein-protein analyzes, to date, around 13 AI-based predictors ( 21 23 , 27 36 ) have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The predictor ( 31 ) was evaluated on data related to 12 viruses, and human proteins. Karabulut et al ( 28 ) proposed meta predictor (ML-AdVInfect) that reaped the benefits of 4 existing predictors namely HOPITOR ( 37 ), InterSPPI-HVPPI ( 31 ), VHPPI, and Denovo ( 29 ). Specifically, the authors passed the predictions of existing predictors to the SVM classifier for the final VHPPI prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods have been developed to predict, integrate and analyze general or virus–human protein–protein interactions at a large scale, where the use of non-structural features is incentivized due to the limited structural coverage ( Andrighetti et al , 2020 ; Ding and Kihara, 2018 ; Dong et al , 2021 ; Karabulut et al , 2021 ; Mahajan and Mande, 2017 ; Wu et al , 2020 ). On the other hand, it was suggested that the structural space is sufficient for protein complex modeling ( Kundrotas et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%